Four Faces of Anger : Seneca, Evagrius Ponticus, Cassian, and Augustine. - Gillette, Gertrude (Lanham : University Press of America, 2010)
This book brings to the modern age wisdom on the topic of anger by four ancient authors: Seneca, Evagrius Ponticus, Cassian, and Augustine. These authors broadly represent the classic views on anger and focus on how anger inhibits spiritual growth of the soul and its relationship with God.
B)taking personal responsibility by admissionc)asking for forgiveness; d)forgiving; e)refraining from being party to others ' enmities; Conclusion; Concluding Remarks; Appendices; Bibliography; Index; About the Author.
Print version record.
Includes bibliographical references (pages 147-152) and index.
Master record variable field(s) change: 600
Keywords: Seneca, Lucius Annaeus, -- approximately 4 B.C.-65 A.D.; Evagrius, -- Ponticus, -- 345?-399.; Cassian, John, -- approximately 360-approximately 435.; Augustine, -- of Hippo, Saint, -- 354-430.; Augustine, -- Saint, Bishop of Hippo; Cassian, John, -- approximately 360-approximately 435.; Evagrius, -- Ponticus, -- 345?-399.; Seneca, Lucius Annaeus, -- approximately 4 B.C.-65 A.D.; Anger -- Religious aspects -- Christianity; Christianity; Anger; Religious Philosophies; FAMILY & RELATIONSHIPS -- Death, Grief, Bereavement; PSYCHOLOGY -- Emotions; Anger -- Religious aspects -- Christianity; Electronic books